Connecting the Classroom with the Newsroom in the Digital Age: An Investigation of Journalism Education in the UAE, UK and USA. (June 2019) - Jiang, Shujun; Rafeeq, Ali
The development of information and communication technology—internet, mobile computing and easier and wider connectivity—is swiftly transforming the news industry. Conventional news production practices have been disrupted and have evolved to meet the needs of a new era of digital and online journalism. In the age of digital and non-linear journalism, the practices of newsgathering, production, distribution and consumption have changed greatly, creating challenges in journalism education. The converged newsrooms of today demand journalism graduates to have digital news production skills that allow them to easily fit into the routines of digital news production practices. By examining the journalism curricula of selected journalism education programmes in the USA, UK and UAE, as well as interviewing journalism educators, students and practitioners, this research investigated whether and how efforts have been made to align journalism curricula to the needs of the industry.